(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2022)
Focus and personal energy during study and work are vital in all learning outputs, especially in the covid-19 time that addresses the importance of self-focused behaviour in online learning environments. In this paper, we present a method of gaining insight into previous knowledge of students’ approaches to focusing and managing personal energy during covid-19 online studying environment to overcome stress. ”Manage your energy, not your time” cites a Harvard Business Review study (Schwartz & McCarthy, 2016), explaining that time management is a waste of time; therefore, we should manage our energy instead. Leaders should focus on managing personal energy and surviving in the workplace to manage stress and achieve a balanced career and private life in the long run. Management course students at the School of Economics and Business, University of Ljubljana, can be perceived as future leaders; we collected their opinions. We used content analysis to estimate how stress affects them and how they manage the consequences of stress, particularly procrastination. The problem with procrastination is that our brains are programmed to procrastinate, especially when it comes to new, unknown tasks. Therefore, our mind responds to postponing the task as fear arises with an unknown task. Results are presented, and key identified themes offer implications for managing physical, emotional, and mental energy. Students perform different cardiovascular sports activities to reduce stress and successfully overcome studying goals in the covid-19 environment.